In Vitro And In Vivo Efficacy Of Fungicides And Biocontrol Agents In The Control Of Fusarium Moniliforme, The Incitant Of Wilt Of Bottle Gourd (Journal of Plant Disease Sciences, 2021)
Bottle gourd (Lagenaria siceraria (Mol.) Stand) is an economically important crop cultivated for vegetable purpose. Wilt incited by Fusarium moniliforme is now days becoming threat to the crop. Henceforth, in vitro and in vivo efficacy of certain fungicides and biocontrol agents tested. Among the different fungicides evaluated, against pathogen, carbendazim 50% WP @ 0.1% and carbendazim 12% +mancozeb 63% WP @ 0.1% completely inhibit the mycelial growth of F. moniliforme and recorded highest disease control 78.57 % and 71.43%, respectively. Among bioagent, Trichoderma harzianum was found most effective with significantly least mycelial growth of pathogen (27.67 mm).
Keywords: Biocontrol; Bottle gourd; Efficacy; Fusarium moniliforme; Fungicides